Food security: state Financial support Measures for sustainable Development of Agriculture in Russian Regions - A. I. Borodin; I. Yu. Vygodchikova; E. I. Dzyuba; G. I. Panaedova (Финансы: теория и практика)
In the context of global economic instability, the problem of ensuring food security and sustainable development of agriculture at the international, national and regional levels becomes urgent. Existing methods for assessing the state of food security and sustainable development of agriculture, as a rule, have two main drawbacks: first, they are often static, and second, they include a scattered list of indicators that are difficult to systematically interpret in the analysis. Therefore, the aim of the study is to develop an adequate methodology for assessing the food security of the constituent entities of the Russian Federation. The construction of a thematic index is carried out in three stages: 1) a system of indicators is formed; 2) the values of indicators are normalized; and 3) sub-indices are calculated. The analysis of domestic and foreign literature on food security provided the methodological basis of the study. The system of indicators was clarified, which were combined into three groups (numerical indicators of the sphere of production, distribution, consumption, and food). The authors extended the retrospective assessment of food security at the meso-level by ranking and clustering Russian regions using hierarchical analysis and a new data filtering algorithm. The hierarchical procedure is based on a system of mathematical filtering of data, which is fundamentally different from existing methods for analyzing hierarchies. The authors replaced the fuzzy “what if” logic with a clear subordination of ranked indicators (subindices). The group of leaders was selected considering the accepted priority of indicators, the rest of the regions were united into a new subgroup, among which leaders and outsiders were singled out. At each new stage, new groups are ranked after excluding leaders and outsiders, they are in the “center of the circular convolution of data”, the procedure for stopping the procedure is the presence of two groups. This is a fundamental feature, scientific novelty, and value of the mathematical apparatus for multidimensional ranking of Russian regions in terms of food security. The authors concluded that in modern Russia the problem of food security has not yet been resolved due to the insufficient use of general economic and special levers to increase the stability of the food system. The results of the study can be applied in the process of updating the state policy in the field of ensuring the sustainability of food systems at the macroand meso-level of management.